THEORETICAL FOUNDATIONS OF ECONOMIC CRISES: CAUSES, FORMS AND CONSEQUENCES (American Journal of Business Management, Economics and Banking, 2025)
This article examines the theoretical foundations of economic crises as an integral element of the dynamics of the market economy. The key economic schools and their views on the nature of crises are analyzed, the main causes of occurrence, forms of manifestation and consequences for various sectors of the economy are systematized. Special attention is paid to the classification of crises by scale, nature and causes, as well as to the examples of crisis phenomena in the world economy. The study is aimed at forming a holistic view of crises as objective phases of the economic cycle and identifying the conditions for overcoming them through rational macroeconomic regulation.